Pore Changes in Purple Mudstone Based on the Analysis of Dry-Wet Cycles Using Nuclear Magnetic Resonance - Chen Dang; Zhili Sui; Xiuyuan Yang; Zhenlong Ge (Shock and Vibration)
The study on the change of rock pore structure during the weathering of purple mudstone is of guiding significance to the stability of the bank slope of the three gorges reservoir. In this paper, the pore changes in the wet and dry circulation of purple mudstone in the three gorges reservoir area are studied by means of nuclear magnetic resonance (NMR). The results show that the simulated weathering of wet and dry circulation has a great influence on the purple mudstone. With an increase in the number of dry-wet cycles, the purple mudstone pore volume ratio significantly changed. Originally, it consisted of a small pore structure with a single pore diameter of 0.01–0.1 µm and changed to a variety of pore structures with various pore diameters of 0.001–100 µm. With the increase in the number of dry-wet cycles, the micropores (0.001–0.1 µm) were transformed into macropores (0.1–1 µm). The area of the second peak of the three samples (large pores 0.1–1 µm) increased from 0.9413, 0.9974, and 0.6779 to 0.9871, 1.1498, and 0.9901, respectively.